Layer-by-Layer Deposition of 2D CdSe/CdS Nanoplatelets and Polymers for Photoluminescent Composite Materials - Li, Fuzhao (Langmuir : the ACS journal of surfaces and colloids, 2022)
Two-dimensional (2D) semiconductor nanoplatelets (NPLs) are strongly photoluminescent materials with interesting properties for optoelectronics. Especially their narrow photoluminescence paired with a high quantum yield is promising for light emission applications with high color purity. However, retaining these features in solid-state thin films together with an efficient encapsulation of the NPLs is a challenge, especially when trying to achieve high-quality films with a defined optical density and low surface roughness. Here, we show photoluminescent polymer-encapsulated inorganic-organic nanocomposite coatings of 2D CdSe/CdS NPLs in poly(diallyldimethylammonium chloride) (PDDA) and poly(ethylenimine) (PEI), which are prepared by sequential layer-by-layer (LbL) deposition. The electrostatic interaction between the positively charged polyelectrolytes and aqueous phase-transferred NPLs with negatively charged surface ligands is used as a driving force to achieve self-assembled nanocomposite coatings with a well-controlled layer thickness and surface roughness. Increasing the repulsive forces between the NPLs by increasing the pH value of the dispersion leads to the formation of nanocomposites with all NPLs arranging flat on the substrate, while the surface roughness of the 165 nm (50 bilayers) thick coating decreases to Ra = 14 nm. The photoluminescence properties of the nanocomposites are determined by the atomic layer thickness of the NPLs and the 11-mercaptoundecanoic acid ligand used for their phase transfer. Both the full width at half-maximum (20.5 nm) and the position (548 nm) of the nanocomposite photoluminescence are retained in comparison to the colloidal CdSe/CdS NPLs in aqueous dispersion, while the measured photoluminescence quantum yield of 5% is competitive to state-of-the-art nanomaterial coatings. Our approach yields stable polymer-encapsulated CdSe/CdS NPLs in smooth coatings with controllable film thickness, rendering the LbL deposition technique a powerful tool for the fabrication of solid-state photoluminescent nanocomposites